Pueblos within Pueblos : Tlaxilacalli Communities in Acolhuacan, Mexico, ca. 1272-1692 - Johnson, Benjamin D. (University Press of Colorado, 2017)
"Systematically analyzing tlaxilacalli history over four centuries, beginning with their rise at the dawn of the Aztec empire through their transformation into "pueblos" of mid-colonial New Spain. Before the Aztecs rise, commoners in pre-Hispanic central Mexico set the groundwork for a new style of imperial expansion"--Provided by publisher.